Temperature dependent polarity inversion in double‐metal terahertz emitters. Issue 16 (1st August 2018) - Gow, P.C.; McBryde, D.; Berry, S.A.; Apostolopoulos, V.
Abstract : The temperature dependent polarity inversion in double‐metal (DM) terahertz (THz) emitters was investigated. DM emitters utilising different metal pairings and single edge metal emitters were cooled in a helium flow cryostat and their THz emission was measured over a range of temperatures. Most emitters, including those with insulating layers between the metal and semiconductor, exhibit a flip in polarity of their THz emission between 50 and 100 K. This shows the inversion is a trait intrinsic to the semiconductor and not influenced by the metallic contact on the surface.